Movements for Schedule Tribe Status in Assam with reference to the Manipuris - Singha, Y Monojit (International Journal of Psychosocial Rehabilitation, 2020)
Safeguarding individual or group interest becomes one of the primary objectives of ethnic communities in modern time. Ethnic mobilization, as an outcome of ethnic politics, remains to be one of the important aspects of the present day socio-political reality in different parts of the world. Here ethnic politics is seen, beside other, mainly as a result of political competition for scarce valued resources and opportunities in societies among ethnic contenders. Thus leads to a system of ethnic stratification in which one ethnic group is dominant over the others, some members from one ethnic group may seek to occupy the privileged socio-economic or political position occupied by the rival ethnic groups. If they fail to do so, they are likely to protest against the system of ethnic stratification as a whole and seek to mobilize their own ethnic group in the hope of getting some privileges for its member vis-à-vis group. Keeping in view of the above, the paper will try to unearth the relation between the ethnic mobilizations in Assam vis-à-vis ethnic politics of the state taking the case of the demand for the ST status by the Manipuris in Assam.